2012
DOI: 10.1111/iej.12025
|View full text |Cite
|
Sign up to set email alerts
|

Study on bending behaviour of nickel–titanium rotary endodontic instruments by analytical and numerical analyses

Abstract: AimTo develop analytical models and analyse the stress distribution and flexibility of nickel–titanium (NiTi) instruments subject to bending forces.MethodologyThe analytical method was used to analyse the behaviours of NiTi instruments under bending forces. Two NiTi instruments (RaCe and Mani NRT) with different cross-sections and geometries were considered. Analytical results were derived using Euler–Bernoulli nonlinear differential equations that took into account the screw pitch variation of these NiTi inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…In addition, its minimum tip size being #30, does not penetrate into apical gutta percha where the apical part is prepared to sizes lesser than #30. Original NRT rotary instruments had a limitation of decreased flexibility, resulting in inability to go around canal curvatures ( 23 ). This may also hold true in case of NRT retreatment files which compromises GP removal efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, its minimum tip size being #30, does not penetrate into apical gutta percha where the apical part is prepared to sizes lesser than #30. Original NRT rotary instruments had a limitation of decreased flexibility, resulting in inability to go around canal curvatures ( 23 ). This may also hold true in case of NRT retreatment files which compromises GP removal efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the ranges of simulated canals with different angles and radii of curvature are large, as is the range of materials examined, which vary from acrylic resin blocks to metal tubes and conformations of canal models using electroerosion. 23,24,25 In this study, a battery of tests was performed to measure flexibility to 45°. In the traction machine, the vertical displacement of the instrument was 15.55 mm, a value obtained using trigonometry (sin 45°).…”
mentioning
confidence: 99%
“…FEA was firstly introduced in endodontics for the static analysis of the forces applied to the NiTi files [15][16][17][18]21]. Afterwards, a dynamic FEA was proposed for the visualization of the instrument mechanical stresses during shaping [17][18][19][29][30][31][32]. In all these studies, the differences found between the instruments were due to the geometry of the instruments and to the alloy stiffness: especially, it was demonstrated how the most rigid instruments caused the highest stress on the apical portion of the canal, confirming that these two instrument characteristics influence their mechanical behavior [4,19,26,33,34].…”
Section: Discussionmentioning
confidence: 99%